Post-traumatic stress disorder among Syrian refugees in Greece - Theofanidis, Dimitrios; Karavasileiadou, Savvato; Almegewly, Wafa Hamad (Frontiers in Psychiatry, 2022)
Background: Post Traumatic Stress Disorder (PTSD) is a psychiatric entity developed by those who have been through a traumatic experience. The civil wars in Syria and neighbouring countries during the past few years might trigger such experiences, and the same could be argued for the difficult journey from the actual war zones to Europe. Purpose: to determine the level of PTSD among Arabic-speaking refugees in a Greek refugee camp, who originate primarily from Syria. Methods: This study involves (N=73) Syrian refugees, all located in Greek camp. Data were gathered using the civilian version of PTSD CheckList (PCL-C). The tool was translated in the Arabic language using standardized back to front techniques. Individual scores were evaluated via use of DSM-IV criteria. SPSS v.21 was employed for the analysis which included descriptive statistics and Fisher’s Exact Test for group comparisons at P≤0.05. Results: PTSD was found in 58 participants, afflicting both genders (72% of men and 45% of women). In addition, the severity score was recorded to be significantly elevated for the majority of the participants. Finally, the most vulnerable age group was the same for both genders, featuring those between the ages of 35 and 44 years. Conclusions: The findings of this study demonstrated that the traumatic experiences, suffered by these refugees either before and/or on their journey to Greece, had a severe mental impact. It is imperative that all refugees suffering from this disorder be diagnosed in time and receive appropriate support. Keywords: Post-Traumatic stress, Refugees, Diagnostic and Statistical Manual of Mental Disorders, Refugee Camps, Syria, Greece